Long-Term Follow-Up of Thyroid Incidentalomas Visualized with 18F-Fluorodeoxyglucose Positron Emission Tomography—Impact of Thyroid Scintigraphy in the Diagnostic Work-Up - Kirsten Korsholm; Michala Reichkendler; Louise Alslev; Åse Krogh Rasmussen; Peter Oturai (Diagnostics, 2021)
Our objective was to evaluate the frequency of malignancy in incidental thyroidal uptake on 18F-fluorodeoxyglucose positron emission tomography/computed tomography (18F-FDG PET/CT) in a cohort of Danish patients, and furthermore to evaluate the impact of thyroid scinti-graphy in the diagnostic work-up. All whole-body PET/CT reports from 1 January 2010 to 31 December 2013 were retrospectively reviewed and further analyzed if visually increased thyroidal FDG uptake was reported. Patient electronic files were searched for further thyroid evaluation. Of 13,195 18F-FDG-PET/CT scans in 9114 patients, 312 PET/CT reports mentioned incidental thyroid FDG-uptake, and 279 patients were included in the study (3.1%). The thyroid was further investigated in 137 patients (49%), and 75 patients underwent thyroid scintigraphy. A total of 57 patients had a thyroid biopsy and 21 proceeded to surgery. Surgical specimens displayed malignancy in 10 cases, and one thyroid malignancy was found by autopsy. Hence, 11 patients were diagnosed with thyroid malignancies among 279 patients with incidental thyroid 18F-FDG uptake (3.9%). In 34 patients, a biopsy was avoided due to the results of the thyroid scintigraphy. We conclude that patients with thyroid incidentalomas can benefit from further diagnostic work-up including a thyroid scintigraphy.